EKSISTENSI BARANG MILIK NEGARA BERUPA GEDUNG PERKANTORAN DI KAWASAN KOMERSIAL: STUDI KASUS DI KAWASAN CBD SUDIRMAN-THAMRIN JAKARTA - Riyanto, Edy; Purnomo, Budi (Politeknik Keuangan Negara STAN, 2019)
Property values in the Sudirman-Thamrin CBD area generally have a higher value compared to property values outside the CBD area, so the decision to build a building in the CBD area needs to consider the level of productivity, especially in financial terms. The Minister of Finance as the State General Treasurer (BUN) feels it is necessary to conduct an analysis of the productivity level of government buildings in the CBD area as material for making policy on State Property in the future. In this analysis, a comparison of the level of productivity from the financial side is presented between 6 (six) government-owned office buildings and 10 (ten) private-owned office buildings. The analysis shows that the government office building from the financial side has a low level of productivity compared to private office buildings located in the Thamrin-Sudirman CBD area.Â